Remote Cardiac Monitoring System (RCMS) - Subramani, Devaa Rani; Huong, Audrey (Evolution in Electrical and Electronic Engineering, 2022)
Cardiac monitoring and rehabilitation is a comprehensive and coordinated program designed to improve cardiac function in patients with heart attack, heart failure, or after heart surgery, or angioplasty. The human population is increasingly concerned about their health condition, especially in this era of the Coronavirus-2019 (Covid-19) pandemic and in the world of fast-growing technology of medical care. This project presents a simple solution for cardiac monitoring that is both economic and easy to use. This is by adopting the Internet of Things (IoT) combined with Arduino-controlled sensors, namely an Electrocardiograph (ECG) sensor (AD8232) and heart rate and pulsatile oxygen saturation (SPO2) sensor (MAX30100), for remote cardiac monitoring. The use of this prototype for cardiac screening required a patient to measure a complete cycle of his/her ECG signal before screen-shooting it for sending by email using MATLAB for online consultation services by a cardiologist or the physician. At the same time, the recordings of the readings are logged into the Cayenne server in near real-time. This allows the cardiologist to monitor the vital sign of the patient remotely. This technology would allow remote monitoring and access to the results using mobile devices, such as mobile phones, tabs, laptops, etc. It is hypothesized that this effective solution would improve the quality of the healthcare delivery process, especially for those living in rural areas where care may be harder to reach.